Pancasila sebagai dasar pembentukan identitas nasional: Kontribusi dalam membentuk kewarganegaraan yang beretika - Asghaf, Almeiza Kanaya (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the contributions of various parties in shaping ethical citizenship, focusing on the roles of individuals, educational institutions, families, and society in instilling ethical values in citizens, using Pancasila as the foundation for national identity formation. The research findings show that collective contributions through ethical education, role modeling, leadership training, and active participation in social activities can produce responsible, tolerant, honest, and patriotic citizens. Therefore, society plays a crucial role in creating a generation that is not only intelligent but also morally and ethically mature, both in urban areas and rural communities.